1982
DOI: 10.1136/hrt.47.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic diagnosis of isolated pulmonary valve endocarditis.

Abstract: SUMMARY A patient is described in whom diagnosis of isolated pulmonary valve endocarditis was made by M-mode and two dimensional echocardiography. Angiography confirmed the presence of vegetations on the pulmonary valve. At cardiac surgery a quadricuspid, non-stenotic valve with ruptured medial leaflet covered by necrotic vegetations and a small ventricular septal defect were found.Echocardiography is known to be useful in diagnosing valvular endocarditisl 2 of the mitral and aortic valves but only two cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[ 5 ] demonstrated that QPV typically persists in normal function throughout the lifetime. However, pulmonary valve replacement [ 70 , 73 , 86 , 87 ] or pulmonary valvuloplasty [ 71 , 74 ] for QPV regurgitation have been reported. The Ross surgery for the congenital anomaly of the pulmonic valve is unfavorable [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] demonstrated that QPV typically persists in normal function throughout the lifetime. However, pulmonary valve replacement [ 70 , 73 , 86 , 87 ] or pulmonary valvuloplasty [ 71 , 74 ] for QPV regurgitation have been reported. The Ross surgery for the congenital anomaly of the pulmonic valve is unfavorable [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 cases of QPV with infective endocarditis were reported. 1 patient with a ventricular septal defect and no stenotic QPV was detected at autopsy [ 70 ]. Additionally, 1 of 13 patients with congenital heart disease and with right-sided infectious endocarditis revealed an isolated QPV [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a report of the echocardiographic diagnosis of pulmonary endocarditis where a small ventricular septal defect was subsequently shown at operation. 18 Subacute bacterial endocarditis must be diagnosed on clinical and bacteriological grounds, but echocardiography is valuable in detecting associated valve lesions. Modem echocardiographic machines can detect vegetations with diameters of > 2-3 mm.…”
Section: Discussionmentioning
confidence: 99%